The relationship between governance practice and earnings quality in Chinese non-profit organisations - ZHU, SHUQI (2019)
This paper examines the relationship between governance practice and earnings quality of Chinese non-profit organisations. To achieve the research objective, this paper selects 100 Chinese non-profit organisations from Chinese Research Data Services Platform (CNRDS) with the data over the period 2012-2016. The empirical research finds that there are only two governance variables which could influence the absolute discretionary accruals, namely dPolitical and CEO_GEN. Specifically, dPolitical has a positive relationship with the earnings quality, and CEO_GEN is negatively related to earnings quality. In addition, there is one control variable (Big10) that is positively correlated with earnings quality. The results indicate that the governance system of Chinese non-profit organisations is weak and it needs to be improved to play its supervisory role.